Pharmacology of grapiprant, a novel EP4 antagonist: receptor binding, efficacy in a rodent postoperative pain model, and a dose estimation for controlling pain in dogs. Issue 3 (6th September 2016) - Nagahisa, A.; Okumura, T.
Abstract : Grapiprant is an analgesic and anti‐inflammatory drug in the piprant class that was approved in March 2016 by FDA's Center for Veterinary Medicine for the control of pain and inflammation associated with osteoarthritis (OA) in dogs. Grapiprant functions as a selective antagonist of the EP4 receptor, one of the four prostaglandin E2 (PGE2 ) receptor subtypes. The EP4 receptor mediates PGE2 ‐elicited nociception, and grapiprant has been shown to decrease pain in several rat inflammatory pain models. It was also effective in reducing pain associated with OA in humans, providing evidence for its mechanism of action in these species. The estimated canine efficacy dose of between 1.3 and 1.7 mg/kg, p.o. with a methylcellulose suspension, once a day, was predicted based on calculations from comparative affinity of grapiprant to the dog, rat, and human EP4 receptors, serum protein binding, effective doses defined in rat models of pain and inflammation, and human clinical studies. The results of this study guided the doses to be tested in the pilot study and demonstrated the usefulness of the efficacy dose prediction method. The approved commercial tablet dose of grapiprant is 2 mg/kg once a day for the control of pain and inflammation associated with OA in dogs.